Flavonoid Glycosides and Hydroxycinnamic Acid Derivatives in Baby Leaf Rapeseed From White and Yellow Flowering Cultivars With Repeated Harvest in a 2-Years Field Study - Groenbaek, Marie; Tybirk, Erik; Neugart, Susanne; Sundekilde, Ulrik Kraemer; Schreiner, Monika; Kristensen, Hanne Lakkenborg (Frontiers in Plant Science, 2019)
Recently, new annual and biennial cultivars of rapeseed with white flowers have been introduced to the baby leaf market. The white flower trait has been bred into modern cultivars of yellow flowering rapeseed. In baby leaf production, it is common practice to perform several cuts of the same plants, thereby harvesting regrown material. Seven white and yellow flowering annual and biennial rapeseed cultivars were harvested as baby leaves, baby leaf re-growths, and intact plants in order to investigate the content of flavonoid glycosides and hydroxycinnamic acid derivatives. The field experiment was conducted over two consecutive years to obtain seasonal differences. The yields and levels of flavonoid glycosides and hydroxycinnamic acids were higher in 2016 than 2017, due to higher temperatures and radiation. Within the growing stage, the effects of flower color, cultivar, and life cycle on flavonoid glycosides and hydroxycinnamic acids varied; however, in general, life cycle was the main influence that resulted in elevated levels of flavonoid glycosides and hydroxycinnamic acids in biennial cultivars, compared to annual cultivars. The effects of the growing stage differed between years, and were influenced by climatic conditions. In conclusion, the choice of life cycle (annual or biennial cultivars) and seasonal effects was of major influence, overruling the effect of developmental stage on the content of flavonoid glycosides and hydroxycinnamic acids.